The Adsorption of Pollutants from Aqueous Effluents Using a Two-Resistance Mass-Transfer Model - G. McKay; J.C. Kelly; I.F. McConvey (Adsorption Science & Technology)
The adsorption of various pollutants, such as phenol, p-chlorophenol and different dyestuffs, on to activated carbon and chitin (a high molecular weight polymer obtained from crustacea) has been investigated in an agitated batch system at a temperature of 18 ± 2°C. Two methods have been used to predict concentration decay curves and correlate theoretical and experimental data. Both methods are based on external mass transfer and internal diffusion as the controlling mass-transfer resistances. The first method is a rapid analytical solution enabling external mass-transfer coefficients and effective diffusivities to be determined, but is restricted to the assumption that a pseudo-analytical isotherm is applicable. The second method, based on a pseudo-analytical solution, is applicable to operating lines and tie lines terminating at any point on the isotherm, but requires longer computational time. Values of mass-transfer coefficients and effective diffusivities are presented for all systems.